LncRNA X‐inactive‐specific transcript is a potential biomarker related to changes in CD4+ T cell levels in systemic lupus erythematosus. Issue 3 (27th September 2022) - Cheng, Qi; Chen, Xin; Xu, Jieying; Chen, Mo; Zhang, Peiyu; Wu, Huaxiang; Du, Yan
Abstract: Background: Systemic lupus erythematosus (SLE) is a particularly heterogeneous autoimmune disease. This study was intended to clarify the correlations between X‐inactive‐specific transcript ( XIST) expression and SLE clinical features and the contribution of XIST to SLE pathogenesis at the transcriptome level. Methods: XIST expression in 79 SLE patients, 14 rheumatoid arthritis patients, and 23 healthy controls was determined by quantitative polymerase chain reaction. The Benjamini and Hochberg adjusted method and multivariate linear regression were applied to correct p ‐values and adjust confounding factors, respectively. Bioinformatic methods were used to explore the function and regulatory mechanism of XIST . Results: XIST was significantly elevated in peripheral blood mononuclear cells and CD4 + T cells from SLE patients compared with the levels in healthy controls and had potential diagnostic value for SLE. Notably, XIST expression was positively correlated with the SLE disease activity index and significantly reduced after effective treatment. Moreover, SLE patients with high XIST expression tended to have elevated levels of CD4 + T cells, but reduced levels of NK cells. Bioinformatic analyses suggested that XIST may regulate OLFM4 and CEACAM8 expression by acting as a spongy body for miR‐20a, miR‐92a, miR‐106a, and miR‐449a . Furthermore, CEACAM8 was significantly upregulated in CD4 + T cells from SLE patients and significantly positively correlated with XIST expression. Conclusions: lncRNA XIST, a potential diagnostic and therapeutic biomarker for SLE, is involved in the change of immune cell balance in the peripheral blood of SLE patients. Mechanistically, XIST may regulate the miR‐17‐92 – CEACAM8 axis to achieve this in CD4 + T cells. Abstract : Seventy‐nine SLE patients, 14 RA patients, and 23 healthy controls were recruited for this study to determine XIST expression in PBMCs and CD4 + T cells. Then, correlations of XIST with clinical traits in SLE patients were performed to understand the biological function of XIST . Bioinformatics methods, including prediction of target miRNAs and genes, construction of a ceRNA network, and functional and pathway enrichment analysis, were used to explore the function and regulatory mechanism of XIST . Finally, we found that XIST may play a biological role in SLE by regulating the miR‐17‐92 cluster and CEACAM8 in CD4 + T cells. ceRNA, competitive endogenous RNA; PBMCs, peripheral blood mononuclear cells; RA, rheumatoid arthritis; SLE, systemic lupus erythematosus; XIST, X‐inactive‐specific transcript. Key points: X‐inactive‐specific transcript (XIST) was significantly elevated in peripheral blood mononuclear cells (PBMCs) and CD4 + T cells from systemic lupus erythematosus (SLE) patients and has potential diagnostic and therapeutic value for SLE. XIST may play a biological role in SLE by regulating the miR‐17‐92 – CEACAM8 axis in CD4 + T cells.